In vitro performance of two-piece zirconia implant systems for anterior application. Issue 6 (June 2016) - Preis, Verena; Kammermeier, Armin; Handel, Gerhard; Rosentritt, Martin
Abstract: Objectives: To investigate the influence of the implant–abutment connection on the long-term in vitro performance and fracture resistance of two-piece zirconia implant systems for anterior application. Methods: Six groups of two-piece zirconia implant systems ( n  = 10/group) with screw-retained (5×) or bonded (1×) connections were restored with full-contour zirconia crowns. A two-piece screw-retained titanium system served as reference. For simulating anterior loading the specimens ( n  = 8/group) were mounted at an angle of 135° in the chewing simulator, and subjected to thermal cycling (TC: 2 × 9000 × 5°/55 °C) and mechanical loading (ML: 3.6 × 10 6  × 100 N). Failed restorations were examined (scanning electron microscopy). Fracture resistance and maximum bending stress of surviving restorations were determined. 2 specimens per group were loaded to fracture after 24 h water storage without TCML. Data were statistically analyzed (ANOVA; Bonferroni; Kaplan–Meier-Log-Rank; α  = 0.05). Results: The bonded zirconia system and the titanium reference survived TCML without any failures. Screw-retained zirconia systems showed fractures of abutments and/or implants, partly combined with screw fracture/loosening. Failure frequency ( F ) varied between the groups ( F  = 8×: 3 groups, F  = 3×: 1 group, F  = 1×: 1 group). The Log-Rank-test showed significant ( p  = 0.000) differences. Fracture forces and maximum bending stresses (mean ± standard deviation) differed significantly (ANOVA: p  = 0.000) between 233.4 ± 31.4 N/317.1 ± 42.6 N/mm 2 and 404.3 ± 15.1 N/549.2 ± 20.5 N/mm 2 . Fracture forces after TCML were similar to 24 h fracture forces. Significance: Screw-retained two-piece zirconia implant systems showed higher failure rates and lower fracture resistance than a screw-retained titanium system, and may be appropriate for clinical anterior requirements with limitations. Failures involved the abutment/implant region around the screw, indicating that the connecting design is crucial for clinical success.